2000
DOI: 10.1074/jbc.275.18.13677
|View full text |Cite
|
Sign up to set email alerts
|

Ras/MEK/ERK Up-regulation of the Fibroblast KCaChannel FIK Is a Common Mechanism for Basic Fibroblast Growth Factor and Transforming Growth Factor-β Suppression of Myogenesis

Abstract: The 10T1/2-MRF4 fibroblast/myogenic cell system was used to address the following interrelated questions: whether distinct signaling pathways underlie myogenic inhibition by basic fibroblast growth factor (bFGF) and transforming growth factor (TGF)-␤; which of these pathways also up-regulates the fibroblast intermediate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
74
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 22 publications
4
74
1
Order By: Relevance
“…The SK3 protein is abundant in porcine coronary endothelial cells, and immunofluorescent labelling confirms that IK1 and SK3 are expressed at the plasmalemma of porcine coronary endothelial cells [21]. In addition, it is well documented that in a number of cell types such as lymphocytes [22] and fibroblasts [23,24], IK1 expression is highly variable during the different phases of cell proliferation. By contrast, in human colonic and cavernosal vascular endothelium, no IK1 immunoreactivity was detected [20].…”
Section: Discussionmentioning
confidence: 60%
“…The SK3 protein is abundant in porcine coronary endothelial cells, and immunofluorescent labelling confirms that IK1 and SK3 are expressed at the plasmalemma of porcine coronary endothelial cells [21]. In addition, it is well documented that in a number of cell types such as lymphocytes [22] and fibroblasts [23,24], IK1 expression is highly variable during the different phases of cell proliferation. By contrast, in human colonic and cavernosal vascular endothelium, no IK1 immunoreactivity was detected [20].…”
Section: Discussionmentioning
confidence: 60%
“…This may be related to the observation that other measures of muscle differentiation appear overall inhibited. This hypothesis is suggested by the observation that TGFB2, a potent inhibitor of skeletal muscle differentiation (22), was up-regulated 9.2-fold, whereas CARM1, MADH3, and NFATC3, all inhibitors of the myogenin͞MyoD pathways, were underexpressed by 1.9-to 4.6-fold (Fig. 4A) (23-25).…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that the expression of IKCa1 is upregulated in all primary pancreatic cancer tissues tested (Jager et al, 2004) and in response to mitogenic activation of the Ras/ERK signaling pathway (Pena et al, 2000). Furthermore, clotrimazole inhibits proliferation of human prostate cancer cell lines, such as LNCaP and PC-3 cells (Parihar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%